Factors influencing vaccination up-take among nomadic population in four regions of Ghana: a qualitative study - Samuel Afari-Asiedu; Lawrence Gyabaa Febir; Charlotte Tawiah; Semeeh Omoleke; Porbilla Ofosu-Apea; Felix Osei-Sarpong; Antoine Marie Cyrille Ziao; Charles Kyei; Edward Anane Apraku; Augustine Antwi; Chrysantus Kubio; Anthony Adofo Ofosu; et al. (BMC, 2024)
Abstract Background Vaccination has contributed to the reduction in vaccine preventable diseases. Despite, improved global coverage, vaccination among nomadic populations is still low especially in Africa. This study explored factors influencing vaccination uptake among pastoralist nomads in Ghana. Methods We conducted key informant interviews (KII) in 11 districts across four regions of Ghana, using grounded theory qualitative research approach. One hundred and eighty-two KII were conducted among pastoralist nomads, community opinion leaders, community health volunteers, security services personnel, local government personnel and health workers. Guided by the WHO health systems building blocks, data was coded using Nvivo 12 and analysed thematically. Results were presented as narratives with excerpts to support the findings. Results Community leaders support vaccination among pastoralist nomads as part of their leadership and governance responsibilities. Language barrier between health workers and pastoralist nomads affects service delivery. Also, healthcare providers fear being attacked by pastoralist nomads hence are hesitant to visit their settlements for vaccination. With regards to health workforce, healthcare providers' perceived use of derogatory words and discrimination against pastoralist nomads influence their vaccination uptake. On medical product, the lack of knowledge about diseases, severity and perceived negative effects about vaccines influence vaccination uptake. Inadequate funds and logistics at the district health directorates affects outreach to nomads during vaccinations. Leveraging existing partnership between the health services and community leaders, information centers, volunteers and butchers to send health information to pastoralist nomads influence vaccination uptake. Conclusion Community leaders support vaccination among pastoralist nomads. Nomadic pastoralist miss vaccination dues to language barrier, feel discriminated against, and lack information about diseases and vaccinations. Strengthening Ghana Health Service collaboration with leaders of pastoralist nomads could build trust, create awareness and overcome language barrier between healthcare providers and pastoralist nomads.